MANAGEMENT OF CARDIAC COMPLICATIONS IN CHAGAS DISEASE - Ferreira, Gledja Akythiara de Araújo; Marchesan, Luis Alexandre Lago; dos Reis, Leandro Costa; dos Santos, Alisom Brito; dos Reis, Vanessa Oliveira; de Souza Júnior, Sílvio Luiz; de Souza, Pablo Andre Brito; Araujo, Kellen de Sousa; Delgado, Lucas Prestes; Becker, Claudia Aparecida; Toledo, Rodolfo Ricardo; Melo e Silva, Débora Filgueiras; et al. (Seven Editora, 2026)
This chapter addresses the management of cardiac complications of Chagas disease (CD), a neglected pathology caused by Trypanosoma cruzi that affects millions and manifests as chronic fibrosing myocarditis, ventricular remodeling, and electrical conduction disorders. The diagnosis of Chagasic Cardiomyopathy (CCD) integrates epidemiological, clinical, and laboratory data, with the electrocardiogram (ECG) being fundamental for screening for alterations, such as the classic finding of right bundle branch block associated with left anterior superior divisional block. Clinical management is staged, and parasitic persistence is the primary mechanism of injury. Etiological treatment with benznidazole or nifurtimox is consensual for acute, congenital cases and reactivations in immunosuppressed individuals, although the BENEFIT study did not demonstrate a significant impact on the progression of ventricular dysfunction in the established chronic phase. Treatment of heart failure (HF) follows general guidelines (ACE inhibitors, beta-blockers, MRAs), with rigorous dose individualization due to the propensity for hypotension and bradycardia. Arrhythmic complications, such as ventricular tachycardia, require amiodarone and, in selected cases, implantation of an automated cardioverter-defibrillator (ICD) to prevent sudden death. Thromboembolism prophylaxis is essential in the presence of atrial fibrillation or apical aneurysms. Reactivation in immunocompromised patients is a medical emergency, requiring quantitative CRP monitoring and immediate treatment. Effective management requires robust evidence, refined clinical judgment, attention to specific situations (congenital transmission, immunosuppression), and the establishment of comprehensive care services to improve quality of life and survival.